CHANGES IN QUALITY INDICATORS OF DIFFERENT CUCUMBER HYBRID SEEDS DURING FIVE YEARS OF AGING: Aging of cucumber seeds during storage - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2023)
The aim of the research was to evaluate the effect of year and seed hybrids on the most significant indicators seed quality of cucumber. Testing the quality of seeds of three different hybrids of cucumber: Centauro F1, Edona F1 and Solatio F1, was carried out during five years (2018 - 2022). Analysis of germination energy, total germination, abnormal seedlings and dead seeds cucumber showed highly significant differences (r<0.01) under the influence of individual factors of year (Y) and hybrid seed (H), as well as their interaction (Y × H). The total germination of the examined hybrids by year slowly decreases and is the lowest at 94% in the fifth year (2022). The strongest positive correlation was established between germination energy and total germination (r = 0.95635, p<0.001) and between abnormal seedlings and dead seeds (r = 0.92301, p<0.001). As expected, a negative and highly significant (p < 0.001) correlation was established between germination energy and: abnormal seedlings (r = -0.94535) and dead seeds (r = -0.93255). Likewise, a strongest negative (p < 0.001) correlation was found between total germination and: abnormal seedlings (r = - 0.97497) and dead seeds (r = -0.98545). The obtained results indicate that the germination energy and total germination of highly hybrid conventional cucumber seeds decreases significantly after the third year of aging, but only in the case of the Edona F1 hybrid. Key words: cucumber, hybrid, germination